Assessment of hypoxia status in a rat chronic liver disease model using IVIM and T1 mapping - Wenlu Dong; Longyang Xiao; Ziwei Luo; Haiyang Yu; Lili Wang; Yuanxiang Gao; Zhiming Li (Frontiers in Medicine)
ObjectivesThis study was aimed to assess the diagnostic performance of intravoxel incoherent motion (IVIM) magnetic resonance imaging (MRI) and T1 mapping in detecting hypoxia status of chronic liver disease using a carbon tetrachloride (CCl4)-induced rat model.Materials and methodsThe hypoxia group of chronic liver disease consisted of eight rats induced by injection of CCl4 and the control group consisted of nine rats injected with pure olive oil. All 17 rats underwent MRI examination at week 13 after injection, using T1 mapping and IVIM. Liver specimens were subjected to immunohistochemical staining for the exogenous hypoxia marker pimonidazole and the endogenous hypoxia marker HIF-1α and scored semi-quantitatively. Differences in MRI multiparameters, pimonidazole H-scores, and HIF-1α were analyzed between the control and hypoxia groups. Correlations between MRI multiparameters and H-score, and MRI multiparameters and HIF-1α, were analyzed, and the diagnostic performance of multiparameter MRI was evaluated by receiver operating characteristic (ROC) curve analysis.ResultsThere were significant differences between the control group and the hypoxia group in D* values (p = 0.01) and f values (p = 0.025) of IVIM parameters, T1 mapping (p = 0.003), HIF-1α (p < 0.001) and pimonidazole scores (p = 0.004). D* (r = 0.508, p = 0.037) and T1 mapping (r = 0.489, p = 0.046) values positively correlated with pimonidazole scores. D* (r = 0.556, p = 0.020) and T1 mapping (r = 0.505, p = 0.039) showed a positive correlation with HIF-1α. The optimal cut-off value of T1 mapping was 941.527, and the sensitivity, specificity, and AUC were 87.5, 77.8, and 0.889 (95% confidence interval [CI]: 0.734–1), respectively.ConclusionIVIM and T1 Mapping are promising methods for non-invasive detection of hypoxia status in chronic liver diseases.